S A Review of DES and AES algorithms for image Encryption - suhad muhajer (Al-Qadisiyah Journal of Pure Science, 2023)
Today the encryption of images has be a requirement to protect a secret image from unauthorized arrival. Different techniques have been presented and sophisticated in spatial, frequency and hybrid domains to encrypt the image securely. Depending on on the security requirements, encryption methods can be classified as full encryption or partial encryption. This paper proposes a review of several image encryption methods  based on AES and DES. The results of previous research have shown that good results in many security analysis such as time execution, entropy, differential attacks, histogram and others. Comparison between AES and DES based on number of factors are presented in this work.